P54 Respiratory symptoms, lung function and quality of life in British foundry workers. (12th November 2015) - Wiggans, RE; Lewis, L; Sumner, J; Robinson, E; Bradshaw, L; Codling, A; Fishwick, D; Barber, CM
Abstract : Introduction: Foundry work is associated with exposure to potentially harmful substances that may cause occupational asthma (OA). Aim: To record respiratory symptoms, lung function and health-related quality of life (HRQoL) in a group of exposed British foundry workers, and investigate their associations and causes. Method: A workplace-based study was conducted, where participants were delivered a researcher-administered questionnaire in order to record individual job exposures, respiratory and general health, and HRQoL (the EQ-5D). Spirometry was performed using a Ndd Easy on-PC Spirometer according to ATS/ERS guidelines. Fractional exhaled nitric oxide (FENO ) was measured using a NOBreath device to ATS standards. Results: 351 (65%) of a possible 539 workers participated. 350 (99.7%) were men, with a mean age of 42.4 (SD 12.5) years. The average length of employment in the foundry industry was 14.8 (SD 12.7) years. Twenty-one (6%) workers self-reported a diagnosis of current asthma, and six (1.7%) self-reported COPD. 139 (40%) participants had at least one respiratory symptom, of which wheeze was the most prevalent (n = 114, 33%). One-in-five participants reported work-related respiratory symptoms (WRRS) (n = 69, 20%), of which work-related cough was the most prevalent (n = 45, 13%; Table 1 ). Significantly more workers reporting WRRS were ever smokers (chi squared = 5.1, p = 0.02). 155 (44%) workers had a FENO above 25 ppb, the suggested ATS cut off for a low probability of eosinophilic airway inflammation. No difference in FENO was found between those with and without WRRS (chi squared for FENO above or below 25 ppb = 1.50, p = 0.22). However, WRRS were associated with significantly lower mean scores on the EQ-5D visual analogue scale (VAS; 77 vs 84, p = 0.001, 95% CI 2.89 – 11.01). In contrast, no difference in VAS was observed between those with and without an obstructive lung defect (FEV1 /FVC <0.7), (mean 83 vs 82, p = 0.63, 95% CI -5.48 – 3.33). Conclusion: Work-related respiratory symptoms among foundry workers were common and associated with impaired HRQoL. More work is required to better understand the cause of such symptoms in foundry workers, and their relationship with workplace exposures.